Aplikasi Protabakter pada Komoditas Tanaman Jagung di Desa Bentok Darat, Kecamatan Bati-Bati - Hiksa Maulana Saputra; Nurhikmah Khairiyah Thahir; Ahmad Khairani; Muhammad A’inul Yaqin; Najwa Norhalida; Nur Afifah; Gizza Anellia Safitri; Siti Nurazizah; Muhammad Syauqi; Andi Muhammad Saputra; Syahrina Nabila Nur Azmi (CV. ITTC INDONESIA, 2026)
Corn commodity farmers in Bentok Darat village, Bati-Bati District, experienced several problems caused by pest attacks, such as caterpillar and grasshopper, downy mildew and root rot. The control that is usually carried out by the community was the use of chemical fertilisers and pesticides that are harmful and not environmentally friendly. Dependence on chemicals is due to the quality assurance of being effective and efficient in controlling problems, but it is dangerous in the long term. This community service activity aims to provide education and assistance about the importance of PGPR and its benefits in increasing growth and protecting the roots of corn plants so that they are not easily attacked by soil-borne diseases, so that dependence on chemicals can be reduced, and the sustainability of the ecosystem can be maintained. The methods used in this community service activity include training and field practice which is carried out in five stages, namely socialization of PGPR biological agent material, demonstration of PGPR product manufacturing, application in corn plantations, observation and evaluation. The activity involved active members of the Sukamaju farmer group who carry out corn commodity cultivation farming business in Bentok Darat Village. The results of field applications show that corn plants applied with PGPR have healthier growth conditions and are not susceptible to disease. These good results make farmers eager to implement PGPR in their farming activities, so that it can reduce farming costs while increasing production and maintaining the sustainability of the agricultural ecosystem.